Respon Siswa Terhadap Penggunaan Modul Mnemonik Dengan Metode RWP (Reading-Writing-Presentation) dalam Pembelajaran Biologi di SMK Analis Kesehatan - Ajeng Mariana Sawitri; Wachju Subchan; Iis Nur Asyiah (Program Studi Magister Pendidikan IPA FKIP Universitas Jember Bekerjasama dengan Perkumpulan Pendidik IPA Indonesia (PPII), 2017)
The purpose of this research was how to know the student's response to mnemonics module with RWP methode in biology leraning in vocational school of healt analyse. Data was taken by questionnaire of student's response that gave after the leraning process with RWP methode end. Data analyse was used by percentage. The first test was took by 34 studensts in XID SMK Analis Kesehatan Jember and the second test was took by 29 students in XIA SMK Analis Kesehatan Jember. The result show that the student's response to mnemonics module with RWP methode in biology leraning in vocational school of healt analyse that the first test had an average for validity of presentation is 96,7%, validity of graphic is 95,5% and validity of mnemonicsis 94,1%. in the second test had an average for validity of presentation is 91,4%, validity of graphic is 91,76% and validity of mnemonicsis 96,6%. Somethings that make the student give the good response to mnemonics module with RWP methode was mnemonics using very familiar, increasing learning motivation, students had opportunity to cooperation in community, they had something new in learning and easy to remember lesson. Keywords: student's response, mnemonics module, RWP method